Innovation Capability as a Catalyst for Improved Service Quality and Work Productivity in Manufacturing - Sasono, Ipang; Yuhelmis; Novitasari, Dewiana; Asbari, Masduki (Journal of Information Systems and Management (JISMA), 2022)
This study investigates the influence of innovation capability and work productivity on service quality within a manufacturing industry in Tangerang, Indonesia. Utilizing a quantitative research design, data were collected through a structured questionnaire distributed to 115 permanent employees, selected via random sampling. The data were analyzed using Structural Equation Modeling (SEM) with the SmartPLS 3.0 software. Results indicate that both innovation capability and work productivity significantly and positively affect service quality. Furthermore, innovation capability also exerts a significant positive influence on work productivity. These findings underscore the pivotal role of fostering innovation capability and enhancing work productivity to improve service quality, thereby equipping companies to compete effectively in the era of Industry 4.0. This research contributes to managerial practices by providing a comprehensive model for optimizing service quality through workforce development strategies, emphasizing innovation and productivity as key drivers.